A species level revision of Bridgerian and Uintan brontotheres (Mammalia, Perissodactyla) exclusive of Palaeosyops - Mader, Bryn J. (Zootaxa, 2008)
A systematic revision based on a morphological and statistical analysis recognizes the following Bridgerian and Uintan brontothere species as valid: Mesatirhinus megarhinus, Metarhinus fluviatilis, Metarhinus diploconus, Sphenocoelus uintensis, Sphenocoelus intermedius, Sphenocoelus hyognathus, Telmatherium validus, Protitanotherium emarginatum, Pseudodiplacodon progressum, Eotitanotherium osborni, Sthenodectes incisivum, and Metatelmatherium ultimum. The valid Bridgerian genus Palaeosyops is not discussed in the present paper. Mesatirhinus, Metarhinus, and Sphenocoelus are grouped within the subfamily Dolichorhininae; Telmatherium, Protitanotherium, Pseudodiplacodon, and Eotitanotherium are grouped within the subfamily Brontotheriinae; and Sthenodectes and Metatelmatherium are listed as Brontotheriidae incertae sedis. It is possible that Metatelmatherium may be a member of the subfamily Brontotheriinae or that it may be closely related to Sthenodectes, justifying the recognition of another North American brontothere subfamily, the Metatelmatheriinae.